2020
DOI: 10.18502/ijrm.v18i2.6423
|View full text |Cite|
|
Sign up to set email alerts
|

Platelet-rich plasma in the management of Asherman's syndrome; An RCT

Abstract: Background: Asherman’s syndrome (AS) is a rare reproductive abnormality, resulting in endometrial collapse due to aggressive or recurrent endometritis and/or curettage. Objective: We aimed to assess the effectiveness of using platelet-rich plasma (PRP) to lower the recurrence rate of intrauterine adhesions (IUAs) following postlysis hysteroscopy. Materials and Methods: In a nonrandomized controlled study, women aged 20-45 years with AS diagnosed by sonohysterography, 3D sonography, hysteroscopy, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 13 publications
0
15
0
3
Order By: Relevance
“…These results suggest that the umbilical cord could be a good source of plasma for treating endometrial pathologies and other regenerative medicine applications, as demonstrated by other groups (Castellano et al, 2017;Ehrhart et al, 2018). PRP has also been tested in women with either thin endometrium (Chang et al, 2019;Eftekhar et al, 2018;Kim, Shin et al, 2019;Molina et al, 2018;Nazari et al, 2016;Tandulwadkar et al, 2017) or AS (Javaheri et al, 2020;Zadehmodarres et al, 2017). However, not all these human works presented a robust study design.…”
Section: Platelet-rich Plasmamentioning
confidence: 89%
See 1 more Smart Citation
“…These results suggest that the umbilical cord could be a good source of plasma for treating endometrial pathologies and other regenerative medicine applications, as demonstrated by other groups (Castellano et al, 2017;Ehrhart et al, 2018). PRP has also been tested in women with either thin endometrium (Chang et al, 2019;Eftekhar et al, 2018;Kim, Shin et al, 2019;Molina et al, 2018;Nazari et al, 2016;Tandulwadkar et al, 2017) or AS (Javaheri et al, 2020;Zadehmodarres et al, 2017). However, not all these human works presented a robust study design.…”
Section: Platelet-rich Plasmamentioning
confidence: 89%
“…However, not all these human works presented a robust study design. From the results obtained by those conducted as clinical trials (Chang et al, 2019;Eftekhar et al, 2018;Javaheri et al, 2020;Tandulwadkar et al, 2017), it could be concluded that PRP is an effective therapeutic option for treating patients with thin endometrium in which the cause is not IUA (this was an exclusion criterion in the majority of existing studies).…”
Section: Platelet-rich Plasmamentioning
confidence: 99%
“…On the contrary, the other study didn't find any significant difference regarding menstrual pattern, duration of menstrual bleeding, and IUAs stage. 21 This study used 1-mL PRP injected into the uterine cavity two days following adhesolysis and after removal of intrauterine balloon.…”
Section: Discussionmentioning
confidence: 99%
“…There are also studies in which the authors did not show that intrauterine PRP injection improves the results of hysteroscopy after surgical removal of intrauterine adhesions [43].…”
Section: Experimental Studiesmentioning
confidence: 94%